2015
DOI: 10.1111/pce.12506
|View full text |Cite
|
Sign up to set email alerts
|

Salt sensitivity in chickpea (Cicer arietinumL.): ions in reproductive tissues and yield components in contrasting genotypes

Abstract: The reproductive phase in chickpea (Cicer arietinum L.) is affected by salinity, but little is known about the underlying cause. We investigated whether high concentrations of Na(+) and Cl(-) in the reproductive structures influence reproductive processes. Chickpea genotypes contrasting in tolerance were subjected to 0, 35 or 50 mm NaCl applied to soil in pots. Flower production and abortion, pod number, percentage of empty pods, seed number and size were evaluated. The concentrations of Na(+) , K(+) and Cl(-)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(74 citation statements)
references
References 40 publications
(89 reference statements)
7
63
0
Order By: Relevance
“…Reproductive phases are considered very important and crop yields and quality is largely dependent on them, but unfortunately the process of reproductive development and grain quality is affected by salinity mostly due to impaired transport of photosynthates to the grain filling site (Kotula et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Reproductive phases are considered very important and crop yields and quality is largely dependent on them, but unfortunately the process of reproductive development and grain quality is affected by salinity mostly due to impaired transport of photosynthates to the grain filling site (Kotula et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…'Exclusion' of Na + is an important mechanism for plants in saline substrates to maintain reasonable leaf Na + concentrations and avoid toxicity to photosynthetic tissues (Munns and Tester, 2008); however we observed that both Na + and Cl − in green leaves or stems of the sensitive genotype (Rupali) were similar or lower compared to those in the tolerant genotypes (JG11 and Genesis836), indicating that ion 'exclusion' does not explain the differences in salt tolerance between these genotypes. A recent study, also having Rupali and Genesis836 when grown in saline soil in pots, also found that salinity tolerance is not linked with genotypic differences in leaf Na + and Cl − concentrations (Kotula et al, 2015). So, it is further hypothesized here that differences in 'tissue tolerance' (of Na + and/or Cl − ) could contribute to the differences in salt tolerance in these chickpea genotypes; as evidenced by higher maintenance of photosynthesis, less leaf damage symptoms (own observations) and greater leaf dry mass in Genesis836 while leaf Na + and Cl − concentrations were similar in the three genotypes (Table 2, Fig.…”
Section: Photosynthesis In Salt Stressed Chickpea Is Limited By Non-smentioning
confidence: 92%
“…The reproductive tissues/processes of JG11 might be particularly salt sensitive (Samineni et al, 2011). However for chickpea (Rupali and Genesis836) in salinized soil, only low concentrations of Na + and Cl − were found in reproductive tissues soon after fertilisation of the ovary (Kotula et al, 2015).…”
Section: Photosynthesis In Salt Stressed Chickpea Is Limited By Non-smentioning
confidence: 99%
“…Nevertheless, NaNO 3 priming alleviated the salinity effect and promoted a reduced K + /Na + content ratio in the roots by reducing the K + content as well as saltresistant species (Fig 8c, e). Therefore, the action of effective priming treatments such as NaNO 3 reaffirms that salinity tolerance is related not only to the presence of higher levels of Na + in the tissue but also to the tolerance of the tissue itself, as highlighted by Khan et al (2015) and Kotula et al (2015).…”
Section: Discussionmentioning
confidence: 99%